A Multiobjective Game Approach with a Preferred Target Based on a Leader-Follower Decision Pattern. (20th March 2018) - Xie, Neng-gang; Chen, Zhong; Cheong, Kang Hao; Meng, Rui; Bao, Wei
Abstract : We propose a multiobjective leader-follower game based on the Stackelberg model, where the designer's preferred target is taken into account. Here, the preferred target is regarded as a leader and the other targets are regarded as followers. A partition method of strategy subspace is also given. Finally, a real-life example of the multiobjective optimization design of a Chinese arch dam named "Baihetan" is presented to demonstrate the effectiveness of our proposed method.